What is the productive potential of digit grass in response to nitrogen fertilization? - Nascimento Fontes, Pryanka Thuyra; Oliveira Santos, Douglas Baracho; Fagundes, Jailson Lara; Backes, Alfredo Acosta; Sousa, Bráulio Maia de Lana; Santos, Luiz Paulo de Souza; Santos, Manoel Eduardo Rozalino (Scientia Plena, 2020)
The digit grass is a highly cultivated species in Northeast Brazil, especially in Sergipe and Alagoas. However, research related to the management of fertilization of this specie is incipient. This experiment was carried out to examine the productive potential of digit grass and its morphological changes in response to nitrogen fertilization. The experimental period was from August 2014 to July 2015. Treatments consisted of five levels of nitrogen fertilization (0, 50, 100, 300 and 600 kg ha-1) arranged in a randomized-block design with four replicates. Urea was used as a source of nitrogen. Height, light interception (LI), leaf area index (LAI), total tiller density (TTD), basal tiller density (BTD) and total (TDM), leaf (LDM) and stem dry matter (SDM) accumulations were influenced (P<0.05) by the nitrogen doses, fitting a positive quadratic equation. Nitrogen fertilization did not influence (P>0.05) dead material accumulation rate or aerial tiller density. Overall, the increasing nitrogen doses culminated in increased canopy height, LI and LAI as a result of the increase in TTD and BTD, which in turn elevated TDM, LDM and SDM. The herbage yield potential of digit grass can be increased with the application of 478 kg N ha-1, enabling its use as an alternative in intensive animal production systems.